Soil organic matter in fire‑affected pastures and in an Araucaria forest in South‑Brazilian Leptosols - Potes, Mariana da Luz; Dick, Deborah Pinheiro; Santana, Graciele Sarante; Tomazi, Michely; Bayer, Cimélio (Pesquisa Agropecuária Brasileira, 2012)
The objective of this work was to evaluate the distribution pattern and composition of soil organic matter (SOM) and its physical pools of Leptosols periodically affected by fire over the last 100 years in South Brazil. Soil samples at 0–5, 5–10, and 10–15 cm depths were collected from the following environments: native pasture without burning in the last year and grazed with 0.5 livestock per hectare per year (1NB); native pasture without burning in the last 23 years and grazed with 2.0 livestock per hectare per year (23NB); and an Araucaria forest (AF). Physical fractionation was performed with the 0–5 and 5–10 cm soil layers. Soil C and N stocks were determined in the three depths and in the physical pools, and organic matter was characterized by infrared spectroscopy and thermogravimetry. The largest C stocks in all depths and physical pools were found under the AF. The 23NB environment showed the lowest soil C and N stocks at the 5–15 cm depth, which was related to the end of burning and to the higher grazing intensity. The SOM of the occluded light fraction showed a greater chemical recalcitrance in 1NB than in 23NB. Annual pasture burning does not affect soil C stocks up to 15 cm of depth.